Qualifying and quantifying of ethanol concentration using plastic optical fibre sensor and spectroscopy techniques / Hasnida Saad - Saad, Hasnida (2018)
Ethanol is the main constituent found in alcoholic beverages and other products that undergo fermentation. Ethanol produced from the fermentation process is totally prohibited for Muslims. From the literatures, the effect of intoxication between synthetic and fermented ethanol is the same. Most global halal organizations have clearly stated that, the minimum concentration of ethanol that can be consumed is 0.5 vol%. The problem with previous researches in POF sensors is the inability to detect ethanol concentration in the range of greater than 0.1 vol% and lower than 5.0 vol%. This lower concentration range is important in determining the halal status of consumer products. A reduction in U-shaped POF bending radius to be smaller than 5.0 cm is proposed to solve the problem based on the work done by F. De-Jun et al. POF with a smaller bending radius that induced more optical loss and interaction to surrounding medium and thus making it more sensitive. After some modifications made to the proposed POF sensor, it was able to detect ethanol concentrations from 0.5 vol% to 15.0 vol% in ethanol-water mixtures. For ethanol concentration above 15.0 vol%, the sensor is less stable and did not produce repeatable results because the physical dimension of the POF has changed. The outer part of the POF swelled due to the high concentration of ethanol. The POF sensor is unable to identify the identity of ethanol compound in visible wavelength region because ethanol is colorless. POF has higher optical attenuation in the UV, NIR and MIR wavelength regions. With these limitations of POF sensor, spectroscopy technique was proposed. Spectroscopy technique has the advantage of identifying the presence of ethanol as compared to the POF sensor. The proposed spectroscopy technique used in the UV, NIR and MIR wavelength regions showed that ethanol can be successfully identified and quantified. However, for estimation of ethanol content in commercial products, only spectroscopy setup at NIR and MIR were measurable. The estimated amount of ethanol in commercial products measured at NIR region is comparable to the amount measured in MIR region. The variance in these two ranges is between 0.2 vol% to 1.7 vol%. The discrepancy between the estimated and the actual ethanol content in the commercial samples measured from spectroscopy technique is believed to be due to the pH effect and the presence of Propylene Glycol compound in mouthwashes. There are two new findings from this research work. A new range limits for detection of ethanol-water mixtures that was successfully measured between 0.5 vol% to 15.0 vol% using an unclad bare U-shaped POF sensor with bending radius of 1.25 cm. The other new finding is on a comparative analysis of ethanol mixtures measured concurrently across UV, NIR and MIR regions using the spectroscopy technique.